Evidence of nickel ions dimerization in NiWO4 and NiWO4-ZnWO4 solid solutions probed by EXAFS spectroscopy and reverse Monte Carlo simulations. (15th September 2021) - Bakradze, Georgijs; Kalinko, Aleksandr; Kuzmin, Alexei
Graphical abstract: Abstract: The existence of exchange-coupled Ni 2 + ions – the so-called magnetic dimers – in wolframite-type NiWO 4 and Zn c Ni 1 − c WO 4 solid solutions with high nickel content was discovered by X-ray absorption spectroscopy combined with reverse Monte Carlo (RMC) simulations. Temperature- (10–300 K) and composition-dependent X-ray absorption spectra were measured at the Ni K-edge, Zn K-edge, and W L 3 -edge of microcrystalline NiWO 4, Zn c Ni 1 − c WO 4 and ZnWO 4 . Structural models were obtained from simultaneous analysis of the extended X-ray absorption fine structure (EXAFS) spectra at three metal absorption edges using RMC simulations. The obtained radial distribution functions for different atomic pairs made it possible to trace in detail the changes in the local environment of metal ions and the effect of thermal disorder. Dimerization of Ni 2 + ions within quasi-one-dimensional zigzag chains of [NiO 6 ] octahedra was evidenced in NiWO 4 in the whole studied temperature range. It manifests itself as the splitting of the Ni–Ni radial distribution function into two separate peaks. The effect is further preserved in solid solutions Zn c Ni 1 − c WO 4 for c ≤ 0.6, which is related to the probability to find two Ni 2 + ions in neighbouring positions.